2021
DOI: 10.1172/jci139481
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophilic inflammation during lung development disrupts elastin assembly and predisposes adult mice to COPD

Abstract: Emerging evidence indicates that early life events can increase the risk for developing chronic obstructive pulmonary disease (COPD). Using an inducible transgenic mouse model for NF-κB activation in the airway epithelium, we found that a brief period of inflammation during the saccular stage [postnatal day (PN)3-PN5] but not alveolar stage (PN10-PN12) of lung development disrupts elastic fiber assembly, resulting in permanent reduction in lung function and development of a COPD-like lung phenotype that progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 71 publications
1
34
0
Order By: Relevance
“…The use of 95% FiO 2 during P1–P4 (saccular stage of lung development) is high. The main reason to restrict the hyperoxia exposure to the first 4 postnatal days was to restrict the hyperoxia exposure during the saccular stage of lung development in mice ( 24 ). This corresponds to 26–36 weeks in human lung development ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…The use of 95% FiO 2 during P1–P4 (saccular stage of lung development) is high. The main reason to restrict the hyperoxia exposure to the first 4 postnatal days was to restrict the hyperoxia exposure during the saccular stage of lung development in mice ( 24 ). This corresponds to 26–36 weeks in human lung development ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is also increasing evidence that NE is a key mediator in BPD, as NE is elevated in BPD airways [129] and has increased enzymatic activity on the surface of neutrophil exosomes obtained from tracheal aspirate of infants with BPD [47]. A recent study using a transgenic mouse model for NFκB activation in the airway found that sublethal inflammation from NE instillation during the saccular stage of lung development, but not during the alveolar stage of development, resulted in a BPD-like lung phenotype of enlarged simplified alveoli, while neutrophil-depleted mice showed normal alveolar structure [130]. NE was also found to be elevated in airways of the mice with lung disease, strongly suggesting that excess NE proteolytic activity leads to aberrant lung development.…”
Section: Ne and Bronchopulmonary Dysplasiamentioning
confidence: 99%
“…Previous studies have demonstrated that an i.p. injection of anti-ly6G antibody in mice resulted in successful depletion of circulating neutrophils as examined by flow cytometry [ 78 , 79 , 80 ]. Thus, to transiently deplete NPs in vivo, a group of mice was injected (i.p.)…”
Section: Methodsmentioning
confidence: 99%